Peran Corporate Governance Sebagai Pemoderasi Hubungan Tax Management dengan Kualitas Laba - Anggreni, Ni Komang; Putra, Nyoman K. A. M.; Yasa, I Nyoman Putra (Journal of Accounting and Investment, 2016)
This study aims to knows the effect of tax management, managerial ownership, institutional ownership to earnings quality a company listed on Indoneisa Stock Exchange. Â This study focused on manufacturing companies listed in Indonesia Stock Exchange for the period 2008-2013. The sampling method used is purposive sampling. Data were analyzed using moderated regression analysis (MRA). The results showed that the tax management negatively affect earnings quality, managerial ownership does not affect the tax relationship management and the quality of earnings and strengthen institutional ownership tax is a negative relationship management to the quality of earnings.